PENGARUH MEDIA VIDEO TERHADAP PENINGKATAN PENGETAHUAN PADA IBU HAMIL ANEMIA - Rahmawati, Eka; Sartika S, Titin Dewi (JOURNAL OF MIDWIFERY SCIENCE, 2021)
Background:The maternal mortality rate (AKI) from 181 countries in the world which ranks first is Indonesia and 28% of the main causes of maternal death are bleeding. One of the main causes of bleeding is anemia. Objective: To determine the use of video media to increase knowledge in anemic pregnant women ibu. Methods: This type of research is quasi-experimental with pre-test and post-test designs with control group design. The population in this study were 87 pregnant women and the sample obtained using the Lemesshow formula to 39 people consisting of two experimental and control groups using accidental sampling research sampling techniques. The research instrument used a questionnaire, video media and leaflet media. Data analysis using paired samples t-test and independent t-test. Results: The results showed that there was an increase in maternal knowledge before and after the intervention of anemia in the experimental group and the control group. For the knowledge of the experimental group with an increase in difference of 36.99 and the control group with an increase in the difference of 13.26 with a p-value of 0.001 (p <0.05).Conclusion: There is an effect of using video media on increasing knowledge of anemic pregnant women. Key words:Video media, knowledge, pregnant women and anemia